Pengaruh Etika Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Budaya Organisasi Sebagai Variabel Intervening Pada CV. Tani Jaya Metro Barat - Durotun Nasikah; Andiana Rosid; Mohammad Nadhif Fadhil (Jurnal Manajemen DIVERSIFIKASI, 2025)
This research aims to determine whether work ethic and work discipline influence employeeperformance with organizational culture as an intervening variable. Quantitative methodswere used in this research. The population in this study were employees at CV. Tani JayaMetro Barat, numbering 50 people. The sampling technique used in this research is themethod for determining saturated samples obtained by the author at CV. Tani Jaya MetroBarat has 50 employees. The data collection technique used was interviews andquestionnaires. Data analysis used includes validity tests, reliability tests, normality tests,linearity tests, homogeneity tests and Path Analysis with the help of the SPSS version 25.0application. The research results can be concluded that there is a direct influence of workethics on organizational culture at CV. Tani Jaya Metro Barat. There is a direct influence ofwork discipline on organizational culture at CV. Tani Jaya Metro Barat. There is a directinfluence of Work Ethic on Employee Performance at CV. Tani Jaya Metro Barat. There is adirect influence of Work Discipline on Employee Performance at CV. Tani Jaya Metro Barat.There is a direct influence of organizational culture on employee performance at CV. TaniJaya Metro Barat.